APPLICATION OF THE COMBINED MEDICATION BASED ON THE MEDICINAL HERBS WITH CODEINE IN TREATMENT AGAINST THE ACUTE RESPIRATORY DISEASES AMONG CHILDREN - V.N. Timchenko; E.B. Pavlova ("Paediatrician" Publishers LLC, 2007)
The article provides the findings of the observation over children (n = 78) aged between 2 and 16 with the acute respiratory infection accompanied by poorly or unproductive cough. 40 patients received the combined medication based on the medicinal herbs with codeine (Codelac Phyto) as the complex therapy. In other cases (n = 38), children received other expectorant medication and/or mucolytics. It shows that the introduction of the combined medication with codeine into therapy of children with acute respiratory infections conduces to faster decrease of the cough intensity and health improvement, as well as the reduction of the unproductive and productive cough duration.Key words: children, respiratory infections, cough, treatment, codeine.